Hubungan Antara Status Gizi Dengan Kualitas Hidup Lansia di Posyandu Lansia di Kecamatan Sanden Bantul - Labiibah, Miftahurrohmah; , dr. Iskandar, M.Kes; , dr. Mohammad Shoim Dasuki, M. Kes (2015)
Background. The growing number of the elderly can lead to a variety of complex problems for the elderly, families and communities include aspects of biological, mental, physical, social or economic. The problems can affect eat intake that will affect the nutritional status. Nutritional status data of elderly in Yogyakarta recorded for malnutrition or underweight Body Mass Index (BMI) is 17.6% which above the national rate, 8.5% overweight, and 10.2% obese, that means same as the national average. Either component in determining the health status of individuals, especially during the aging process, is the quality of life. Elderly who are malnourished will increase morbidity, mortality and decrease the quality of life. Methods. This study type uses observational analytic cross-sectional approach. The study was conducted at Puskesmas Sanden territory at October 2015 - November 2015. The sample was comprised of 97 eldery, in the eldery posyandu (Intergrated Health center) at Puskesmas sanden Bantul. The variables of study include: nutritional status and the eldery quality of life. The nutritional status data was obtained from BMI by measuring weight and height. The eldery quality of life data obtained by the WHOQOL-Bref questionnaire. The statistical test used is the Chi square test. Results. Proportion of the good quality of life higher in the elderly group with a normal nutritional status which compared with the elderly group with nutritional status of malnourished (91.7%: 12.0%, p = <0.001; p <0.05), which means there is a significant relationship between nutritional status and the elderly quality of life in the elderly posyandu in the Sanden sub-district Bantul. Conclusion. There is a significant relationship between nutritional status with the elderly quality of life in the elderly posyandu at Sanden sub-district Bantul